The Islamic Education Reform Early 20th Century - M. Fahim Tharaba; Mukhibat Mukhibat (AL-TAHRIR, 2020)
Abstract: The Islamic education reform comprises a change that affects people’s choice of education as an agent of change and human and capital investment. Thus, it is a need to modernize the thought of renewing Islamic education according to the time’s advances. The study of the Islamic education reform in early 20th century has become relevant in the context of valuable lessons for reform and or modernization of Islamic education in subsequent developments. This research employed a philosophical and implemental approach. It was bibliographic research with the content analysis of the meaning and substance contained in the whole thought about the reform of the Islamic education in early 20th century. This study found that there were three patterns of renewal of Islamic education; (1) modern orientation in Europe, (2) the refinement of Islamic teachings, and (3) nationalism reform. The concept of Islamic education reform encompasses all ideas that are guided by the Qur’an and Sunnah, and continues to follow the times consciously and systematically and directed towards the interests that refer to the progress of science and technology, and based on faith and devotion (IMTAQ). The reform of the Islamic education system has included both the conceptual-theoretical and operational-practical levels, as well as the fundamental aspects that underlie the students’ lives; it is monotheistic faith which has a monolatry dimension of piety to God. It encourages and ignites to play a real role in all aspects of life.الملخص: إصلاح التعليم الإسلامي هو شكل من أشكال التغيير الذي يؤثر على اختيار الناس للتعليم كعامل للتغيير والاستثمار البشري ورأس المال. فلذلك, يجب تحديث فكرة مجددي التعليم الإسلامي دائما وقفا بالزمان الواقع أومما هو أبعد وأجدد منه. أصبحت دراسة إصلاح التعليم الإسلامي في أوائل القرن العشرين مناسبا وأكثر اهتماما من أجل استكشاف التجارب القيمة أو المعلومات أو الإمكانات المتعلقة بتطوير التعليم الإسلامي في المستفبل. استخدم الباحث المنهج الفلسفي والمنهج التنفيذي على أنواع ببليوغرافية مع تحليل محتوى المعنى والمضمون المتضمن في جميع التفكير حول إصلاح التعليم الإسلامي في أوائل القرن العشرين. وجد الباحث في هذا البحث على الأقل ثلاثة انماط لتجديد التربية الإسلامية. الأول كمنحى التحديث في أوروبا, والثاني للتخليص التعاليم الإسلامية, والثالث كالتحديث الوطنية. يشمل مفهوم إصلاح التعليم الإسلامي جميع المفاهيم التي يسترشد بها القرآن والسنة ويثبت في متابعة الزمان وتشير إلى تقدم العلم والتكنولوجيا على أساس الإيمان والتقوى بالله. يشمل تحديث نظام التعليم الإسلامي كلا من المستويات المفاهيمية النظرية والعملية الواقعية بالإضافة إلى المفاصل الأساسية التي تؤسس حياة الطلاب وهو الإيمان والتوحيد بالله تعالى من أجل تشجيع وتحفيز الطلاب ليلعب دورا حقيقيا في جميع مجال الحياة.Abstrak: Reformasi pendidikan Islam merupakan bentuk perubahan yang mempengaruhi pilihan masyarakat terhadap pendidikan sebagai agent of change dan human and capital investmen. Maka, pemikiran pembaharuan pendidikan Islam harus selalu dimodernisasi sesuai bahkan melampaui perkembangan zaman. Kajian reformasi pendidikan Islam awal abad-20 ini menjadi sangat relevan dalam rangka pelajaran berharga untuk reformasi dan atau modernisasi pendidikan Islam dalam perkembangan selanjutnya. Penelitian dengan pendekatan filosofis dan implementatif ini bersifat penelitian bibliografic resarch dengan content analysis terhadap makna dan substansi yang terkandung dalam keseluruhan pemikiran tentang reformasi pendidikan Islam awal abad-20. Kajian ini menemukan setidaknya ada tiga pola pembaharuan pendidikan Islam; (1) oreintasi modern di Eropa, (2) untuk pemurnian kembali ajaran Islam, (3) pembaharuan bersifat nasionalisme. Konsep reformasi pendidikan Islam meliputi segala konsep yang berpatok kepada al-Qur’an dan Sunnah, dan tetap mengikuti perkembangan zaman yang secara sadar dan sistematis serta terarah pada kepentingan yang mengacu pada kemajuan ilmu pengetahuan dan teknologi (IPTEK), dan dilandasi dengan keimanan dan ketaqwaan  (IMTAQ). Pembaharuan sistem Pendidikan Islam  telah mencangkup baik pada tataran konseptual-teoritis maupun operasional-praktis,  serta sendi-sendi fundamental yang mendasari kehidupan peserta didik, yaitu iman tauhid yang berdimensi ketakwaan yang monoloyal kepada Allah, dalam rangka mendorong dan memacu untuk berperan nyata dalam semua lini kehidupan.